In reply - Bärtsch, Peter; Schommer, Kai (Deutsches Ärzteblatt, 2012)
We thank our correspondents for their comments and critical remarks, which enable us to explain the most important points raised in some more detail. We were asked to provide a review article that enables general practitioners to grasp the basics of...
Gesehen am 03.12.2018